Psychoeducation group for parents who raise a child with autism spectrum disorder - Mukhtar, Desvi Yanti; Hastjarjo, T Dicky; Kumara, Amitya; Adiyanti, M G (COUNS-EDU: The International Journal of Counseling and Education, 2018)
The aim of the research is to know how the impact of psychoeducation group to the level of parenting stress of parents who raise a child with autism spectrum disorder. This research used quasi experimental method with the design of the untreated control group with dependent pretest and posttest samples. This research involved 25 parents  (20 mothers and 5 fathers) who raise a child with autism spectrum disorder divided into two groups, experimental group and  the control group. The experimental group has received psychoeducation treatment with ecological approach for two months (8 meetings, conducted once a week). This research used Scale of Parenting Stress, observation, test of knowledge about parenting of children with autism spectrum disorder, and sheet of evaluation of psychoeducationactivities  in collecting the data. The result of the analysis with mixed anovahave shown that psychoeducation group has no effect to the level  of parenting stress (F = 0,697 p > 0,05). The result of check manipulation have shown that the knowledge of subject on parenting of children with autism increase after join in the psychoeducation group.